Analysing the effectiveness of pictograms as a hazard communication mechanism to reduce child exposure to chemicals in South Africa - Louw, Tatum (Department of Public Health and Family Medicine, 2021)
Hazard communication mechanisms are essential for informing child caregivers of the dangers associated with chemical products. However, for caregivers to protect their own health and their children from the harm of toxic chemicals, it is important that they understand label information as scientifically intended. Therefore, to accommodate parts of society that have a lack of access to education, the placement of hazard communication pictograms on labels have been introduced to overcome literacy barriers. Many research studies have been conducted on the comprehensibility of pictograms and have found that many barriers exist in end-users being able to understand the intended message behind the pictogram. This study, therefore, explores further the awareness and comprehension of pictogram comprehensibility among caregivers in South Africa that have different backgrounds and living experiences. The study employed a mixed-methods cross-sectional design. The study was conducted with farmworkers from a farm in Paarl and students from the University of Cape Town. Two different data collection tools were used: a face-to-face questionnaire was administered to farmworkers (taking into account literacy barriers) and an online questionnaire to students due to unforeseen circumstances (COVID-19), that put a pause on face-to-face questionnaires being administered among UCT students. Both groups received the same questions except for small adjustments made to the online questionnaire to accommodate the platform. Data for the face-to-face questions were stored in the data collection application, CommCare, and transferred to Excel for quantitative analysis. The online questionnaire was administered through a Google form that was emailed to all students at the university by the Department of Student Affairs and data were then transferred to excel for quantitative analysis. The qualitative data were analysed using a thematic analysis approach where themes were created from theory in the literature and word repetitions that emerged from the respective group responses. Based on the overall results, comprehension of the pictograms varied greatly between caregiver groups indicating harmonization is necessary. Although beyond the scope of this study, the difference amongst the perception of danger warrants further analysis on whether age, educational level, perception of danger, lived experiences, and environmental exposure play a role in the two groups' comprehension of pictograms. The study focused on the already existing Globally Harmonized System of Classification and Labelling of Chemicals (GHS) pictograms as well as newly proposed ones to communicate the “Keep out of reach of children” message. Based on the overall results, what the pictograms represented varied greatly between the different caregiver groups, indicating that comprehension differs largely, and harmonization has not been entirely achieved as desired by the GHS. However, the study concludes that participants place responsibility on the chemical industry to make information about the harmful effects about their products more accessible to communities through educational talks, social media, experts at the point of sale to explain any potential hazards, and through the use of billboards and flyers. Though difficult to achieve, it is suggested that conversation amongst chemical legislators and industry commence on how to include the voice of end-users in the development and implementation of hazard communication strategies.